FOCUSING IN THE MESSAGES OF IMAM ALI BETWEEN THE IDEALISM OF ONE'S OWN SELF AND THE INFERIORITY OF THE OTHER - Ph. D Kadhim Fakhir Hajim; Assist. Lecturer Khaleda Ali Falih (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Concentration as a critical concept is closely related to authority with its different levels and seeks to prove itself and degrade the other, especially the other who steps out of his or her circle. The conflict between Imam Ali as the center and the other as the rebellious margin represented one of the tools or manifestations of power and it was from here that the idea arose to convey Imam Ali's messages to his governors, workers and emirs about the Islamic State in his government to determine the nature of the relationship between them, the center as an example of authority and the rebellious other as the fringe, beyond their control.